Therapeutic Alliance in the Personal Therapy of Graduate Clinicians: Relationship to the Alliance and Outcomes of Their Patients. (18th February 2014) - Gold, Stephanie H.; Hilsenroth, Mark J.; Kuutmann, Klara; Owen, Jesse J.
<x xml:space="preserve">Abstract</x> This is the first study to explore the relationship between aspects of a therapists' personal therapy and the subsequent psychotherapy process and outcome they perform. The participants were 14 graduate clinicians with various experiences in personal therapy, who treated 54 outpatients engaged in short‐term psychodynamic psychotherapy at a university‐based community clinic. Results demonstrated non‐significant relationships between the duration of personal therapy as well as a graduate clinician's overall alliance in their personal therapy with alliance ratings made by themselves as therapists and their patients, as well as the number of psychotherapy sessions attended by patients. However, the clinician's personal therapy alliance was significant and positively related to their patients' rating of outcome. Additionally, a significant negative correlation was observed between the degree of perceived helpfulness in their personal therapy and how these clinicians rated alliances, as the therapist, with their patients. The current findings suggest a relationship between a clinician's personal therapy alliance and the outcome of treatments they conduct. Implications for clinical training and practice as well as future research are discussed. Copyright © 2014 John Wiley & Sons, Ltd. Key Practitioner Message While graduate clinician's personal therapy alliance was not significantly related to their patients' ratings of alliance, it was related to their patients' ratings of outcome. Trainee satisfaction with or quality of their personal therapy may be a more relevant than the amount or duration of their treatment in regard to the process and outcomes of their patients. The findings from retrospective clinician surveys on the helpfulness of their personal therapy may not be entirely consistent with empirical examination of these issues. The relation of personal therapy and outcome may work through improving the therapist's level of adaptive functioning (i.e., psychological‐relational‐emotional health) and future research should examine this simpler, more parsimonious, explanation for our findings.